Konflik Pemerintah Daerah dan Kelompok Adat; Studi Kasus Peraturan Penataan Lembaga Adat dan Kebudayaan Daerah Kabupaten Gowa Tahun 2016 - Shujahri AM, Muh. (Global and Policy Journal of International Relations, 2018)
This paper discusses the political conflict between the regional government of Gowa Regency, represented by Regent Adnan Yasin Limpo and the family of Gowa Kingdom by Andi Maddusila after the enactment of the Regional Regulation on the Arrangement of the Regional and Customary Cultural Institutes of Gowa Regency in 2016. This research is qualitative research. This study found that the conflict occurred because the LAD Regional Regulation affected the power network of the Gowa royal group, namely the change in access to property of the Kingdom of Gowa such as the BallaLompoa palace and customary land and created changes in the network structure of the kingdom with the emergence of new adat institutions. The author concludes that this regulation is the final round of conflicts between the Limpo clan and the Andi Madusila clan. Through the Local Regulation of LAD, a network of powers that guarded Andi Maddusila's power over a period of seventeen years was cut off. In the absence of access to royal power on Andi Maddusila's side it was difficult for Andi Maddusila's group to consolidate the power of the royal family in Gowa Regency. Keywords: political conflict, local political elite, LAD Constitution, Gowa RegencyDOI: https://doi.og/10.33005/jgp.v6i02.1823